Control of the vegetative growth of ’Shinseiki’ pear trees by prohexadione calcium and root pruning - Carra, Bruno; Fachinello, José Carlos; Abreu, Everton Sozo de; Pasa, Mateus da Silveira; Spagnol, Daniel; Giovanaz, Marcos Antônio; Silva, Carina Pereira da (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the effect of prohexadione calcium (P-Ca) and root pruning (RP) on the control of the vegetative growth and on fruit production and quality of 'Shinseiki' pear trees, under the climatic conditions of Southern Brazil. The experiment was conducted during the 2013/2014 and 2014/2015 crop seasons, in a 15-year-old orchard of 'Shinseiki' pear trees, trained to a central-leader system, with a 2x5 m spacing between plants, grafted onto Pyrus calleryana rootstock. The experiment was carried out in a randomized complete block design, with six treatments and four replicate. The treatments consisted of the control (without P-Ca application or RP), two P-Ca rates (300 and 600 mg L-1), two root pruning intensities (performed on one or on both sides of the tree), and root pruning on one side + 300 mg L-1 P-Ca. P-Ca reduced vegetative growth more effectively than RP, in both crop seasons, and the combination of both techniques did not result in additional control of the vegetative growth, compared with P-Ca alone. Vegetative growth was not affected by increasing the rates of P-Ca. The highest P-Ca dose negativelly affected fruit yield. Regarding fruit quality, RP increases the total soluble solids content at harvest.